A Review on the Book "Ministry System in the Abbasid Government (Al-Buyeh and Seljuk Era) - Seyyed Mohammad Rahim Rabbanizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The ministry system is one of the consolidating pillars of every government. Any government with a strong bureaucratic system has a higher stability, and the Abbasid government had a bureaucratic-ministerial system, more evident in the Al-Buyeh and the Seljuks era. In order to explain the role of the Department of Justice, a lot has been written. One of them is the book "The Ministry System in the Abbasid Government (Al-Buyeh and Seljuk era)" written by Zahrani. The present study attempts to critically review the above book with an interpretative and problem-centered approach and the findings suggest that although Zahrani addresses the importance of the ministry system, he also narrates the same information in the style of the earlier ones and that he raises a general model for the research organization based on which he analyzes the whole book, leading to limitations in providing a better analysis, and ultimately he deals with the role of the minister himself as an individual than investigating him in the form of a system.